Operational State Evaluation of Wind Power Gearbox based on Grey Cloud Model Clustering and Cloud Gravity Center Theory - Wang Hongjun; Zhao Yuanlu; Zhao Hui; Yue Youjun (Jixie chuandong)
Aiming at the problems of insufficient comprehensiveness and low accuracy in evaluating the operation status of wind power gearbox, an evaluation method based on grey cloud model clustering analysis and cloud gravity center deviation theory is proposed. A relatively complete evaluation system for wind power gearbox can effectively improve the accuracy of the evaluation results is established. A preliminary clustering analysis of the gearbox is carried out by using the grey cloud model, and the general evaluation results of the current operation of the wind power gearbox are obtained. On this basis, the cloud gravity center offset of standard cloud model and current cloud model is calculated, which further improves the reliability of the evaluation results. Through the state evaluation of the real wind power gearbox measurement data and comparing with the gear box record state, it is proved that the proposed evaluation method has certain accuracy and usability value.